Gas Chromatography-Mass Spectrometry (GC-MS) Analysis of Bioactive Components of Ethyl acetate Root Extract of Guiera senegalensis J.F. Gmel - Shettima AY, Karumi Y, Sodipo OA, Usman H and Tijjani MA (Journal of Applied Pharmaceutical Science, 2013)
Guiera senegalensis J.F. Gmel is used in West African Ethnomedicine for treating diarrhoea, dysentery, malaria, cough and microbial infections. The methanol and ethyl acetate root extracts of G. senegalensis have been shown to be effective against diarrhoea and also have antibacterial activity. The plant was therefore investigated for its bioactive components. The ethyl acetate root extract was investigated using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Nine components were identified, n-Hexadecanoic acid (46.6%) as the major component followed by 9-Hexadecenoic acid (20.93%), methyl ester (7.75%), 7-Octadecenoic acid- methyl ester, 1, 2-benzene dicarboxylic acid – diisoctyl ester having (6.97%) respectively; 2–pentanone - 4–hydroxy–4–methyl acid diethyl phthalate (2.32%), Decane–6–ethyl–2–methyl and nonane, 3–7–dimethyl with (1.55%) compositions respectively.
Keywords: G.senegalensis, Ethyl acetate, GC